Synthesis engineering of iron oxide raspberry-shaped nanostructures. Issue 1 (2nd December 2016) - Gerber, O.; Pichon, B. P.; Ihiawakrim, D.; Florea, I.; Moldovan, S.; Ersen, O.; Begin, D.; Grenèche, J.-M.; Lemonnier, S.; Barraud, E.; Begin-Colin, S.
Abstract : The formation mechanism of rapsberry-shaped nanostructures with the identification of two iron precursors: the starting one and an intermediate and in situ formed iron alkoxide precursor with a plate-like lamellar structure contributing to the heterogeneous growth step. Abstract : Magnetic porous nanostructures consisting of oriented aggregates of iron oxide nanocrystals display very interesting properties such as a lower oxidation state of magnetite, and enhanced saturation magnetization in comparison with individual nanoparticles of similar sizes and porosity. However, the formation mechanism of these promising nanostructures is not well understood, which hampers the fine tuning of their magnetic properties, for instance by doping them with other elements. Therefore the formation mechanism of porous raspberry shaped nanostructures (RSNs) synthesized by a one-pot polyol solvothermal method has been investigated in detail from the early stages by using a wide panel of characterization techniques, and especially by performing original in situ HR-TEM studies in temperature. A time-resolved study showed the intermediate formation of an amorphous iron alkoxide phase with a plate-like lamellar structure (PLS). Then, the fine investigation of PLS transformation upon heating up to 500 °C confirmed that the synthesis of RSNs involves two iron precursors: the starting one (hydrated iron chlorides) and the in situ formed iron alkoxide precursor which decomposes with time and heating and contributes to the growth step of nanostructures. Such an understanding of the formation mechanism of RSNs is necessary to envision efficient and rational enhancement of their magnetic properties.